Unveiling the Data Revolution: A Comprehensive Analysis of Big Data’s Impact Across Industries - Davis, Olivia; Carter, Ethan (Journal of Science & Technology, 2021)
In the era of information abundance, this research paper endeavors to unveil the intricate tapestry of the data revolution and its profound impact across diverse industries. The paper navigates the challenges and opportunities posed by the data revolution, exploring not only the technical aspects of data analytics but also the ethical considerations and societal implications of wielding such vast amounts of information. From predictive analytics driving business foresight to the societal impacts of data-driven decision-making, our analysis encompasses the multifaceted dimensions of big data’s influence. This paper serves as a valuable resource for academics, industry professionals, and policymakers seeking a comprehensive analysis of big data’s impact across industries, offering insights that extend beyond the realm of technology to shape the future of how businesses and societies harness the power of data.